2020
DOI: 10.3233/jad-200940
|View full text |Cite
|
Sign up to set email alerts
|

Death Rate Due to COVID-19 in Alzheimer’s Disease and Frontotemporal Dementia

Abstract: We aimed to evaluate the frequency and mortality of COVID-19 in patients with Alzheimer’s disease (AD) and frontotemporal dementia (FTD). We conducted an observational case series. We enrolled 204 patients, 15.2% of whom were diagnosed with COVID-19, and 41.9% of patients with the infection died. Patients with AD were older than patients with FTD (80.36±8.77 versus 72.00±8.35 years old) and had a higher prevalence of arterial hypertension (55.8% versus 26.3%). COVID-19 occurred in 7.3% of patients living at ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 11 publications
6
57
1
Order By: Relevance
“…A total of 8 studies were further removed because they were not original articles, 2 studies were removed because the population was not in older adults with dementia who have COVID-19, 19 studies were removed because they didn't provide the result of the mortality, and 2 studies were removed because they didn't provide full-text article. Finally, 15 studies were included in the systematic review 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 . The selected studies are presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 8 studies were further removed because they were not original articles, 2 studies were removed because the population was not in older adults with dementia who have COVID-19, 19 studies were removed because they didn't provide the result of the mortality, and 2 studies were removed because they didn't provide full-text article. Finally, 15 studies were included in the systematic review 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 . The selected studies are presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the selected studies are summarized in Table 3 , which indicates that the included studies came from 7 different countries. Six of the studies were conducted in Italy 19 , 20 , 21 , 22 , 4 were conducted in Spain 27 , 28 , 32 , 33 , and 1 study per country was conducted in Belgium 23 , France 24 , South Korea 25 , Turkey 26 , and Japan 29 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, AD was the most common diagnosis for cognitive impairment in the confirmed COVID-19 group (9.3% of all patients) [63]. More importantly, another observational study in Spain reported a higher proportion of COVID-19-infected cases in the AD population (15.1%) [64]. Given this evidence, AD appears to be an important influential comorbid of COVID-19.…”
Section: Ad Patients Exhibit Elevated Morbidity and Mortality Of Covid-19mentioning
confidence: 95%
“…Data collected from a tertiary hospital in Spain showed that subjects with cognitive impairment had shorter survival from the onset of symptoms than patients without cognitive impairment [63]. Furthermore, significantly higher death rates were observed in COVID-19 patients with AD (54.5%), than in patients with FTD (χ 2 = 4.94, P = 0.045), suggesting that the progression of AD correlates with the severity of COVID-19 [64]. In addition, a Korean team has evaluated the contribution of various factors, such as age, AD, chronic lung disease, stroke, hypertension, coronary vascular disease, dyslipidemia, chronic kidney disease, diabetes, and history of taking angiotensin II receptor blockers or ACE inhibitors, to the death rate of COVID-19 patients in a multicenter retrospective cohort, using multivariate logistic analysis, and found that only age, AD, and chronic lung disease are significant parameters for predicting COVID-19 non-survival (P < 0.05) [65].…”
Section: Ad Patients Exhibit Elevated Morbidity and Mortality Of Covid-19mentioning
confidence: 97%
“…Concomitantly, the risk of exposure to the infection is more important in patients with dementia, highly exposed in the context of long-term care facilities, frequent hospitalizations and intellectual decline. So far, speci c clinical features and prognostic factors of COVID-19 in demented patients remain unclear [6,7].…”
Section: Introductionmentioning
confidence: 99%